868. Prospective Pathogen Detection in Patients With Central Nervous System Inflammation Using Metagenomic Sequencing. (26th November 2018) - Piantadosi, Anne; Mukerji, Shibani; Ye, Simon; Leone, Michael; Freimark, Lisa; Lemieux, Jacob; Solomon, Isaac; Ahmed, Asim; Kanjilal, Sanjat; Goldstein, Robert; Ganesh, Vijay; Ostrem, Bridget; et al.
Abstract: Background: Metagenomic sequencing can identify pathogens in patients with central nervous system (CNS) inflammation, who often have no diagnosis achieved despite extensive clinical testing. Methods: This prospective study enrolled patients with CNS inflammation at a tertiary hospital from 2016 to 2017. Total nucleic acid was extracted from cerebrospinal fluid (CSF). Libraries were constructed by random primer cDNA synthesis from RNA, and Nextera XT preparation from both cDNA and DNA. Sequencing was performed on an Illumina platform. Reads from human and environmental contaminants were removed. Metagenomic analysis was performed with Kraken and confirmed with viral-ngs. The Institutional Review Board approved the study, and informed consent was obtained. Results: Of 68 subjects enrolled, 63% were men and 84% were white. The median age was 58 years. The median CSF pleocytosis was 80 cells/mm 3 [IQR 17–132]. A median of 2.4 million RNA and 6.8 million DNA sequencing reads were generated per sample. Twenty-five subjects had no diagnosis achieved by routine clinical testing; metagenomic sequencing identified enterovirus in 2 of these subjects, and no pathogen in 23. Thirty-six subjects were clinically diagnosed with an infection. In 12 of these, pathogen nucleic acid was detected in CSF by clinical polymerase chain reaction (PCR); metagenomic sequencing detected the expected pathogen in 10 subjects (83%). The other 24 subjects were clinically diagnosed with infection by serology or PCR from blood. Among these, metagenomic sequencing detected the CSF presence of HIV and locally important tick-borne pathogens Powassan virus, Borrelia burgdorferi, and Anaplasma phagocytophilum . Four subjects with West Nile Virus (WNV) infection did not have WNV RNA detected in CSF by sequencing or clinical PCR testing. Among 7 subjects diagnosed with malignancy or autoimmune disease, no pathogens were detected by metagenomic sequencing. Conclusion: When applied broadly to patients with CNS inflammation, metagenomic sequencing identified known and unexpected pathogens in CSF, including emerging tick-borne pathogens, highlighting its potential as a diagnostic tool. Patients in whom no pathogen nucleic acid was detected could have had an infection with low pathogen burden or short duration in CSF, or a noninfectious syndrome. Disclosures: All authors: No reported disclosures.